Chemovirotherapy of malignant melanoma with a targeted and armed oncolytic measles virus - Kaufmann, Johanna K.; Bossow, Sascha; Großardt, Christian; Hassel, Jessica C.; Kalle, Christof von; Enk, Alexander; Nettelbeck, Dirk M.; Ungerechts, Guy (The journal of investigative dermatology, 2013)
Effective treatment modalities for advanced melanoma are desperately needed. An innovative approach is virotherapy, in which viruses are engineered to infect cancer cells, resulting in tumor cell lysis and an amplification effect by viral replication and spread. Ideally, tumor selectivity of these oncolytic viruses is already determined during viral cell binding and entry, which has not been reported for melanoma. We engineered an oncolytic measles virus entering melanoma cells through the high molecular weight melanoma-associated antigen (HMWMAA) and proved highly specific infection and spread in melanoma cells. We further enhanced this oncolytic virus by inserting the FCU1 gene encoding the yeast-derived prodrug convertases cytosine deaminase and uracil phosphoribosyltransferase. Combination treatment with armed and retargeted MV-FCU1-αHMWMAA and the prodrug 5-fluorocytosine (5-FC) led to effective prodrug conversion to 5-fluorouracil, extensive cytotoxicity to melanoma cells, and excessive bystander killing of noninfected cells. Importantly, HMWMAA-retargeted MV showed antitumor activity in a human xenograft mouse model, which was further increased by the FCU1/5-FC prodrug activation system. Finally, we demonstrated susceptibility of melanoma skin metastasis biopsies to HMWMAA-retargeted MV. The highly selective, entry-targeted and armed oncolytic virus MV-FCU1-αHMWMAA may become a potent building block of future melanoma therapies.